Acute Pulmonary Thromboembolism: A Retrospective Study in a Nigerian Private Tertiary Hospital - Ogunkoya JO; Oluwole AO; Adefuye BO; Adebola-Yusuf AO; Ehioghae O (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2021)
Background: Pulmonary embolism (PE) is a disease associated with high morbidity and mortality in the more technically advanced western world. However, in Africa and Nigeria in particular, the burden of PE is largely poorly defined as few data are available. Objectives: To characterize the clinical profile, management and outcomes in PE patients confirmed with Computerized Tomography Pulmonary Angiography (CTPA). Methods: A retrospective study was conducted at Babcock University Teaching Hospital, Ilishan-Remo, Nigeria. The medical records of PE patients confirmed by CTPA and admitted to the intensive care unit of the hospital spanning July 2016 to June 2020 were retrieved for analysis. Results: Thirty-one patients with the age range of 26 to 93 years were included and the mean age was 55.5±18.5 years. Breathlessness was the most prevalent presenting symptom. In the majority of patients (48.4%), the risk factors were not known. However, the most common risk factor and co-morbidity was pregnancy (16.1%). The in-hospital mortality rate was 9.7%. Conclusion: The clinical characteristics of PE in this cohort were similar to those described in the literature. The high mortality rate in this study also underscores the need for large population studies in black Africans.